2018
DOI: 10.1177/2054358118775098
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Self-Management Resources Used by Canadian Chronic Kidney Disease Clinics: A National Survey

Abstract: Background:Chronic kidney disease (CKD) clinics across Canada provide tailored care for patients with CKD with an aim to slow progression and prevent complications. These clinics provide CKD self-management resources; however, there is limited information about what resources are being used by clinics. We undertook a survey of CKD clinics across Canada to identify self-management resources for adults aged 18 years and over with CKD categories 1 to 5 and not requiring dialysis or transplant.Objective:To identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 8 publications
(12 reference statements)
0
13
0
Order By: Relevance
“…7 Five patient partners and 1 caregiver were engaged in the previous phases of this work, including a scoping review, a survey of chronic kidney disease clinics, analysis of behaviours of patients with chronic kidney disease and caregivers by means of the Theoretical Domains Framework and a qualitative study. 5,6,8,9 This has laid the foundation for the present study. Based on the qualitative study, 8 topic areas were identified -understanding chronic kidney disease, diet, medications, symptoms, finances, mental and physical health, travel and work/school -as well as features including mixed-content formats (e.g., visuals, text, user-generated content).…”
Section: Openmentioning
confidence: 91%
See 2 more Smart Citations
“…7 Five patient partners and 1 caregiver were engaged in the previous phases of this work, including a scoping review, a survey of chronic kidney disease clinics, analysis of behaviours of patients with chronic kidney disease and caregivers by means of the Theoretical Domains Framework and a qualitative study. 5,6,8,9 This has laid the foundation for the present study. Based on the qualitative study, 8 topic areas were identified -understanding chronic kidney disease, diet, medications, symptoms, finances, mental and physical health, travel and work/school -as well as features including mixed-content formats (e.g., visuals, text, user-generated content).…”
Section: Openmentioning
confidence: 91%
“…5 Traditionally, self-management interventions for patients with chronic kidney disease have included education and support through face-to-face interactions, with minimal use of electronic health (e-health) tools (e.g., websites, mobile apps, short-messaging service). 6 The use of e-health tools, including the Internet, mobile-phone-based apps, computer-based tools and mixed-mode tools, may enhance patient self-management. Although e-health tools will not replace the provider-patient relationship, they are a potential platform to augment support for chronic kidney disease self-management.…”
Section: Openmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is informed by our previous work using a collaborative and systematic approach to determine the best practices for CKD adult self-management support interventions [7,13,[15][16][17]. Specifically, our work is guided by the integrated knowledge translation (IKT) method [18] and the Canadian Institutes of Health Research (CIHR) Strategy for Patient-Oriented Research (SPOR) patient engagement principles [19].…”
Section: Previous Workmentioning
confidence: 99%
“…Many individuals with CKD receive self-management education and support through face-to-face interactions in the clinic setting [ 7 ]. However, with increasing access to the internet [ 8 ] and the nature of pandemics, the potential for an eHealth platform to provide easy access and timely, tailored information and support could be a sustainable way to enhance self-management strategies.…”
Section: Introductionmentioning
confidence: 99%